Performing similarity analysis on organic farming crop data of Turkish Cities - Kaşif, Ahmet; Ortaç, Gizem; Ibis, E.; Bilgin, Turgay Tugay (Institute of Electrical and Electronics Engineers Inc., 2020)
Organic crop production is an important technique which can help increase the quality and throughput of food production. In this study, similarity analysis of organic farming crop data of Turkish cities has been performed. The dataset has been collected from the web site of Turkish Ministry of Agriculture and Forestry. Some pre-processing techniques have been applied. Dynamic Time Warping distance has been used as a similarity metric. Results show that Dynamic Time Warping similarity is suitable for similarity detection of organic crop production. © 2020 IEEE.
2020 Innovations in Intelligent Systems and Applications Conference, ASYU 2020 -- 15 October 2020 through 17 October 2020 -- -- 165305
Keywords: dynamic time warping; organic food production; similarity; time series